Uma proposta de manejo para a pesca do Polvo Octopus Insularis Leite & Haimovici, 2008 (MOLLUSCA: cephalopoda) no arquipélago de Fernando de Noronha, Brasil - Leite, Tatiana Silva (2008)
The Fernando de Noronha Archipelago is consolidating a fishery/environmental policy which should be able to guarantee the conservation of its natural resources, including the shallow-water octopus. Recently, studies about biology, fishery and ecological importance of the more abundant octopus species, namely Octopus insularis Leite & Haimovici, 2008 should provide the data framework to support the management of its exploitation. The gathered information indicate that the small-scale fishery at the actual level is consistent with resource conservation. To guarantee that the fishery impact will not increase, some measures should be implemented, such as: the restriction of the fishery license only for native fishermen and residents with more than 10 years living in the FNA, to set up a 80 mm mantle length as the legal minimum catch size, protected areas with less than 2-meter depths, since they are used as nursery areas, and to forbid fishing with traps and irritant substances. Those recommendations have been taken into account by the Brazilian Management Authority for the regulation of the octopus fishery inside of Preservation Area of the Fernando de Noronha Archipelago since 2005.